Testing the visual-motor coordination and reaction speed in children aged between 10-14 years old - Dan Alexandru SZABO; Andreea Roxana UJICĂ; Ovidiu URSU (Editura Universităţii din Oradea, 2021)
The present study aimed to debate a topic less addressed by most people, which involved research on a group of 20 students from rural areas, aged 10-14 years, which consists of performing two tests, namely the Ruler drop test and the Hand-eye coordination test, which aims at the reaction speed of the dominant and non-dominant hand and also the hand-eye coordination capacity of the subjects. The paper aimed to identify whether somatic factors and age influence the results of the group. In order to perform the two tests, it was necessary, for the beginning, information related to the study group, information on weight, age, height, dominant hand, respectively dominant eye. These represented the point of interest of the research, being reported individually to the test results, thus constituting the study basis of statistics. After obtaining the results, we concluded that a significant significance is encountered when comparing the dominant hand with the non-dominant one, obtaining a positive value for the dominant hand. At the same time, we interpreted after the research that females tend to have a much faster reaction speed, more significant than the males when it comes to using the non-dominant hand. The hypothesis was confirmed, with differences in somatic factors' influence, but the others do not show significant values except those stated above. In addition to the practical part, the research involves an interesting theoretical foundation being reached aspects related to proprioception, coordination, speed, ways of using tests, and the opinion of other researchers who have conducted similar studies.